1999
DOI: 10.1111/j.1365-2141.1999.01329.x
|View full text |Cite
|
Sign up to set email alerts
|

Defective human T‐lymphotrophic virus type I provirus in T‐cell prolymphocytic leukaemia

Abstract: T-cell prolymphocytic leukaemia (T-PLL) is a rare form of post-thymic T-cell neoplasm, the aetiology of which remains unknown. We examined human T-lymphotropic virus (HTLV) provirus in five HTLV-I/II seronegative patients with T-PLL. Southern blotting did not show monoclonal integration of the HTLV-I genome in any of the DNA samples. However, two of the five DNA samples contained an HTLV-I tax sequence. Other sets of oligonucleotide primers for HTLV-I gag, pol, env and LTR regions were all negative. HTLV-I tax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The deletion would eliminate the donor sites for the mRNAs of the proteins encoded by the tax gene [14], and, indeed, serum levels of C-PTHrP in the two cases were not elevated (28.7 and 35.4 pmol/l). Normal serum C-PTHrP levels in these cases were in agreement with the previous findings of no tax gene expression in cases with the sequence [10]. In contrast to ATL, in which various serum markers provide useful therapeutic and prognostic information, it is not known whether serum parameters have valuable clinical information for patients with T-PLL.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The deletion would eliminate the donor sites for the mRNAs of the proteins encoded by the tax gene [14], and, indeed, serum levels of C-PTHrP in the two cases were not elevated (28.7 and 35.4 pmol/l). Normal serum C-PTHrP levels in these cases were in agreement with the previous findings of no tax gene expression in cases with the sequence [10]. In contrast to ATL, in which various serum markers provide useful therapeutic and prognostic information, it is not known whether serum parameters have valuable clinical information for patients with T-PLL.…”
Section: Discussionsupporting
confidence: 88%
“…Patients with T-PLL are commonly seronegative for HTLV-I and have no functionally active proviral HTLV-I DNA in their leukemia cells [10,11]. Hypercalcemia does not develop in patients with T-PLL.…”
mentioning
confidence: 98%
“…Moreover, findings about seronegative HTLV-1 carriers have been described in groups of TSP/HAM patients from different countries, 3,5 in HTLV-1 infected patients with MF 10,11 and their relatives 11 in addition to subjects with ID 7 or hematological diseases. [20][21][22] This is the first report of seronegative profiles in symptomatic and asymptomatic HTLV-1 infected subjects in Argentina. Our results indicate that prevalence rates of HTLV-1/2 infection settled down by serology could be underestimated and corroborate the strong silent dissemination of HTLV-1 infection in Northern Argentina, as we have previously reported.…”
Section: Discussionmentioning
confidence: 79%
“…However, we were unable to detect antibodies in the patient's serum, perhaps as a result of severe immunosuppression owing to the long-standing disease and adverse effects of the prolonged chemotherapy. Seronegativity of patients infected with HTLV-1 has been reported previously [16,36] and often related to defective viral genome [13,24] and to suboptimal levels of HTLV-1 for antibody responses [17]. Additionally, it has been suggested that HTLV-1 might play a role in the induction of severe immunosuppression and high rate of infections by altering T lymphocyte immune function [2,18,22].…”
Section: Discussionmentioning
confidence: 98%